THE EFFECTIVENESS OF THE QUR'ANI SIDOGIRI METHOD IN IMPROVING THE ABILITY TO READ AL-QUR'AN AT THE KANZUS SHOLAWAT BOARDING SCHOOL IN JATI KULON KRAKSAAN. - Inayah, Nur; Arisanti, Kustiana; Ulfah, Yeniati (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
This study aims to analyze the effectiveness of the Qur'ani Sidogiri Method in improving students' Qur'an reading skills at Kanzus Sholawat Islamic Boarding School, Kandang Jati Kulon, Kraksaan. This qualitative descriptive research uses a case study approach. Data were collected through interviews, observation, and documentation. The findings show that the method is implemented gradually using a talaqqi system and tiered levels, requiring students to pass evaluations before advancing. This method effectively improves students' reading skills in fluency, makhraj, letter characteristics, and tajweed. Students respond positively; they feel supported, motivated, and better understand the material. Supporting factors include the talaqqi approach, progressive evaluations, and teacher motivation, while challenges include varying initial abilities. The study concludes that the Qur'ani Sidogiri Method is effective when applied adaptively and consistently in the pesantren setting.